Contract administration procedure for World Bank funded construction projects in Afghanistan - Saljoqi, Khalid; Santoso, Djoen San; Hadikusumo, Bonaventura H. W.; Chotchai Charoenngam; AFG Western Basins Water Resources Management Project; AIT Fellowship (Bangkok : Asian Institute of Technology, 2017)
Ineffective contract administration procedures plays a vital rolein typical construction problems such as extensive delays in planned schedule cost overruns, very serious problem in quality, and an increased number of claim and litigation. Due to the different culture in each country, Afghan contract administration procedures were investigated from World Bank construction projects. This study was conducted by focusing on contract administration procedures during construction phase as payment, request extension o time, submittal and approval, inspection, change order, and delay procedures.Date was included contract conditions and clauses from case study World Bankconstruction project. In addition, the supportive information was collected through personal interview. The in-depth experienced consultant was interviewed based on the data provided from the contract conditions in order to get more reliable information. The obtained data was analyzed to indentify the contract administration procedures during the construction phase in practice from World Bankby using the frequency distribution statistical analysis. Also, the strengths and weaknesses of each procedure can be determined via personal interview.
A research submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Construction, Engineering and Infrastructure Management
Research report (M. BA.) - Asian Institute of Technology, 2017
Keywords: Construction projects -- Management -- Afghanistan; Public contracts -- Afghanistan